Proposed new interior design of Pasar Budaya Taiping for Majlis Perbandaran Taiping (MPT) at Jalan Chung Thye Phin Taiping, Perak / Amirah Rozani - Rozani, Amirah (Faculty of Architecture, Planning and Surveying, 2011)
The final semester for an Interior Design student is mostly spent for the final year project. Almost the whole four months are rigorously spent for this project alone. For my final project, I have proposed a new interior design scheme for ‘Pasar Budaya’ Taiping for Taiping Municipal Council (MPT) at the Old Market, Jalan Chung Thye Phin, Taiping, Perak. The Taiping Municipal Council has a plan to upgrade the existing market building into a tourist attraction, the center of a cultural hub. The whole area is to become a ‘pedestrian mall’ where visitors -locals or tourists, can walk around and experience the rich history on the streets of Taiping. This proposal will hopefully be a model for other cultural markets or bazaars. The aim of this research is to be able to understand the system of a cultural market and the best way to design one. It should be beneficial to its users in terms of good design, flow efficiency, comfort and aesthetic value. These aspects need to be covered to meet the client’s vision of the new ‘Pasar Budaya’. Plenty of research needed to be done to gather information regarding similar projects. The space requirements, clients’s requirements and structural and cultural limitations are important facts to consider. With the building’s own historical value, it is crucial to maintain the bustling atmosphere and the feel of being in a colonial-style Malaysian city. Taiping is already marketed as a tourism destination so a new breath of life into its old walls would be a good change, at the same time, preserving what has been part of Taiping locals’ everyday life.